Respostas

A melhor resposta!
2014-03-19T18:00:06-03:00


a) x²-3x+1   com x=4
 fica

4²-3.(4)+1 =

16 - 12 + 1= 5


b) a³+b³-2a²+4ab+1 com a=2 e b=-3

2³+(-3³)-2.(2²)+4.(2.-3)+1

8-27-2.(4)+4.(-6)+1 =

8-27-8-24+1 =  -50

2 5 2
2014-03-19T18:16:51-03:00
X² - 3x + 1 =
4² - 3 · 4 + 1  =
16 - 12 + 1 = 5 


a³ + b³ - 2a² + 4ab + 1 =
2³ + ( - 3 ) - 2 · 2 + 4 · 2 · ( - 3 ) + 1 =
8 - 3 - 4 + 8 - 3 + 1 = 7


2 5 2
iiih esqueci de calcular o 3 ao cubo e o 2 ao quadrado :/
a³ + b³ - 2a² + 4ab + 1 =
2³ + (-3)³ - 2 · (2)² + 4 · 2 · (- 3) + 1 =
8 - 9 + 2 · 4 + 24 + 1 =
- 1 + 8 + 24 + 1 = 32
menos três ao cubo é -27 e não -9